A Network-Based Dynamic Analysis in an Equity Stock Market. (27th November 2017) - Eberhard, Juan; Lavin, Jaime F.; Montecinos-Pearce, Alejandro
Abstract : We study how changes in the structure of a brokers' transaction network affect the probability with which the returns and volume of the traded financial assets change significantly. We analyze how the dynamics of the brokers' transaction network are associated with the returns and volume observed in the Chilean stock market. To do this, we construct and validate an index that synthesizes the daily changes of the brokers' transaction network structure of equity market transactions. We find that the changes of this structure are significantly correlated with variables that describe the local and international economic-financial environments. In addition, changes in the brokers' transaction network structure are associated with a greater probability of positive shocks of more than two standard deviations in the stock exchange index return and total traded stock volume. These results suggest that the structure of the brokers' trading relations plays a role in determining the returns and volume of transactions in the Chilean stock market.